Language Functions and Styles Used by Vendors at Legian Beach - Sidabutar, Riris; Sadia, I Gede (Humanis, 2018)
As social beings, we interact each other. One kind of interaction is by communicating. In communicating, we need language so that we can convey our ideas, desires, intentions and purposes to others. This is called language function. The functions of language are important in our live. According to Bruce Tillit and Mary Newton Brother, there are eleven functions of language we usually use in our daily conversation. They describe it in their book entitled: Speaking Naturally: Communication Skill in American English (1985). Besides of language functions, there is another thing which also has important role in communication that is language styles. We can know the background of a person through the style of the language he/she used. According to Martin Joos (1976,) there are five types of language styles, whereas according to Mandell and Kirzner (2003), there are four types of language styles. This study aims to analyze the language functions used by vendors at Legian beach as well as to find the style of language they use in their conversations with tourists. The results of this research indicate that eight of the eleven language functions proposed by Bruce Tillit and Mary Newton Bruder were used by vendors at the Legian beach in their conversations with tourists. The most common language functions they use are the language functions of getting information and controlling the conversation. There are four types of language styles they use in communicating with tourists. From those four styles of language, they mostly used informal style.